A twin-axial pseudorotaxane for phosphorescence cell imaging. Issue 10 (8th January 2021) - Ma, Xin-Kun; Zhang, Ying-Ming; Yu, Qilin; Zhang, Haoyang; Zhang, Zhiyuan; Liu, Yu
Abstract : A twin-axial pseudorotaxane is constructed using a phenylpyridine salt with diethanolamine (DA-PY) and cucurbit[8]uril (CB[8]), and it not only displays phosphorescence in aqueous solution but it can also be used for targeted cell-imaging. Abstract : A twin-axial pseudorotaxane is constructed using a phenylpyridine salt with diethanolamine (DA-PY) and cucurbit[8]uril (CB[8]), and it not only displays phosphorescence in aqueous solution but it can also be used for targeted cell-imaging.